Effects of Burkholderia pseudomallei and other Burkholderia species on eukaryotic cells in tissue culture. - Harley, V; Dance, D; Drasar, B; Tovey, G (1998)
Burkholderia pseudomallei causes melioidosis, a serious and often fatal bacterial infection. B. pseudomallei can behave as a facultatively intracellular organism and this ability may be important in the pathogenesis of both acute and chronic infection. The uptake of B. pseudomallei and other Burkholderia spp. by cells in tissue culture was examined by electron microscopy. B. pseudomallei can invade cultured cell lines including phagocytic lines such as RAW264, J774 and U937, and non-phagocytic lines such as CaCO-2, Hep2, HeLa, L929, McCoy, Vero and CHO. Uptake was followed by the intracellular multiplication of B. pseudomallei and the induction of cell fusion and multinucleate giant cell formation. Similar effects were produced by B. mallei and B. thailandensis.